Deterministic and stochastic factors jointly drive plant community composition and diversity in isolated wetlands - Claire M. Ciafré; C. M. Gienger; Evan M. Rehm; L. Dwayne Estes (Wetlands, 2022)

Improving species status assessments under the U.S. Endangered Species Act and implications for multispecies conservation challenges worldwide - Reed F. Noss; Jennifer M. Cartwright; Dwayne Estes; Theo Witsell; Gregg Elliott; Daniel Adams; Matthew Albrecht; Ryan Boyles; Patrick Comer; Chris Doffitt; Don Faber‐Langendoen; JoVonn Hill; et al. (Conservation Biology, 2021)
Despite its successes, the U.S. Endangered Species Act (ESA) has proven challenging to implement due to funding limitations, workload backlog, and other problems. As threats to species survival intensify and as more species come under threat, the need for the ESA and similar conservation laws and policies in other countries to function efficiently has grown. Attempts by the U.S. Fish and Wildlife Service (USFWS) to streamline ESA decisions include multispecies recovery plans and habitat conservation plans. We address species status assessment (SSA), a USFWS process to inform ESA decisions from listing to recovery, within the context of multispecies and ecosystem planning. Although existing SSAs have a single‐species focus, ecosystem‐based research can efficiently inform multiple SSAs within a region and provide a foundation for transition to multispecies SSAs in the future. We considered at‐risk grassland species and ecosystems within the southeastern United States, where a disproportionate number of rare and endemic species are associated with grasslands. To initiate our ecosystem‐based approach, we used a combined literature‐based and structured World Café workshop format to identify science needs for SSAs. Discussions concentrated on 5 categories of threats to grassland species and ecosystems, consistent with recommendations to make shared threats a focus of planning under the ESA: (1) habitat loss, fragmentation, and disruption of functional connectivity; (2) climate change; (3) altered disturbance regimes; (4) invasive species; and (5) localized impacts. For each threat, workshop participants identified science and information needs, including database availability, research priorities, and modeling and mapping needs. Grouping species by habitat and shared threats can make the SSA process and other planning processes for conservation of at‐risk species worldwide more efficient and useful. We found a combination of literature review and structured discussion effective for identifying the scientific information and analysis needed to support the development of multiple SSAs. Article impact statement : Species status assessments can be improved by an ecosystem‐based approach that groups imperiled species by shared habitats and threats.

Carex fumosimontana (Cyperaceae), a new endemic from the Great Smoky Mountains National Park, North Carolina and Tennessee - Dwayne Estes (Brittonia, 2013)